The Differences In The Occurrence Of Drug-Related Problems And The Duration Of The Assessment Of Pediatric Chemotherapy Prescriptions Before And After The Implementation Of The Electronic-Based Cytotoxic Drug Reconstitution Guidance System At Dr. Moewardi Hospital: Pharmaceutical Installation of Dr. Moewardi Hospital - Pridiyanto; Agus Suryadi, Bambang; Shaffira, Mutthia; Zaroh, Fatimah (Indonesian Basic and Experimental Health Sciences, 2025)
Abstract. Introduction Assessment of pediatric chemotherapy prescriptions is essential for preventing Drug-Related Problems (DRPs). A preliminary review showed that 57% of pediatric injectable chemotherapy patients were at risk of potential DRPs, contributing to prolonged assessment times. These issues indicate the need for systematic improvements to enhance medication safety and workflow efficiency. This study aimed to evaluate differences in DRP incidence and prescription assessment duration before and after implementing an electronic cytotoxic reconstitution guidance system. Method An experimental design was used to compare assessments before and after implementation of the electronic guidance system. A total of 60 pediatric chemotherapy prescriptions were analyzed, consisting of 30 assessed without the system (control) and 30 assessed after implementation (treatment). DRP occurrences were documented, and assessment duration was measured in minutes and seconds. Statistical analyses were performed to identify differences between groups, with significance set at P < 0.05. Results In the control group, 26 DRPs were identified, compared with 6 in the treatment group. Statistical analysis confirmed that the guidance system significantly reduced DRP incidence (P < 0.05). The mean assessment duration also decreased substantially from 7 minutes 2 seconds before implementation to 3 minutes 18 seconds afterward, and this reduction was statistically significant (P < 0.05). Conclussion The electronic cytotoxic reconstitution guidance system effectively enhances the safety and efficiency of pediatric chemotherapy prescription assessments. It significantly reduces DRP incidence and shortens assessment duration, demonstrating its value in improving workflow and supporting safer chemotherapy services.